Prevalence and Demographic Profile of White-coat Hypertension in the Patients Visiting a Tertiary Care Center in Eastern Nepal - Ghimire, Jeet; Karki, Biplave; Nepal, Bikash; Mahaseth, Aditya; Sah, Ajit; Pandit, Swapnil; Pandey, Naveen; Shah, Prashant; Karki, Prahlad (Nepal Mediciti Medical Journal, 2022)
BACKGROUND: There is unequivocal evidence showing that at hospital environment BP levels are usually different from measures found at other settings. Therefore, ambulatory BP is expected to be more dependable, as well as allow the identification of a relevant subgroup of white-coat hypertension patient.METHODS: This was a single center descriptive cross-sectional study conducted to assess the prevalence of white-coat hypertension among 50 participants consisting of 31 males and 19 females referred for 24 hour Ambulatory BP monitoring in BPKIHS, Dharan, Nepal, between October 2021 to December 2021.RESULTS: The prevalence of white-coat hypertension was 19 (32%) among 50 participants, while 31(62%) of them had sustained hypertension. Prevalence of WCHTN and sustained hypertension in young age ≤35 years was 4 (21.1%) and 10 (32.3%) respectively, similarly middle age 36-54 years was 13(68.4%) and 16(51.6%) and elderly ≥55 years was 2(10.5%) and 5(16.1%) respectively. Most participants were of middle age group 36-54 years’ age. While of sex distribution pattern of WCHTN and sustained hypertension, male was 11(57.9%) and 20 (64.5%) respectively and female was 8(36.8%) and 15(48.4%) respectively. The association between the demographic variables age, sex and BMI and white-coat HTN was not statistically significant.CONCLUSION: The study showed that White-coat hypertension was more common in male patients and in middle age group 36-54 years, but was not statistically significant. Prevalence of white-coat hypertension was 19(38%). There was no significant association between white-coat hypertension and demographic variables.